Essential and non-essential elements in the bowhead whale: epidermis-based predictions of blubber, kidney, liver and muscle tissue concentrations - O'Hara , Todd M.; Hanns , Cyd; Woshner , Victoria M.; Zeh, Judy; Bratton, Gerald; Taylor, Robert (J. Cetacean Res. Manage., 2023)
Assessment of element concentrations in wildlife must address both nutritional and toxicological considerations. The liver, epidermis, muscle and kidney of the bowhead whale are rich in some essential and non-essential elements. Blubber tends to have lower concentrations of these elements. Various cetaceans have been evaluated for these elements using a variety of sample sources (live and dead stranded whales, bycaught animals, remote and capture-release biopsy techniques, hunter killed whales etc). One constant shared by these approaches is the sampling of epidermis and adjacent dermis (blubber). In this study, the ability of elemental concentrations in bowhead whale epidermal samples to predict the corresponding elemental concentrations in blubber, kidney, liver and muscle is investigated. Epidermal concentrations had no predictive value for copper (Cu), manganese (Mn), lead (Pb), selenium (Se) or zinc (Zn) in any of the other tissues evaluated, except that the epidermal measurement provided an upper bound for blubber concentration of Cu, Mn, Se and Zn. Epidermal concentrations of the four other elements considered were predictive for some other tissues. Arsenic (As) concentrations could be predicted in kidney, liver and muscle but not blubber, although the preponderance of samples with concentrations below the minimum level reported (MLR, also known as ‘detection limit’) and the small sample sizes that resulted from their omission suggest that these data should be interpreted with caution. Epidermal concentrations of cadmium (Cd) were strongly predictive for blubber and weakly predictive for muscle concentrations. Epidermal concentrations of mercury (Hg) were weakly predictive of blubber, liver and muscle concentrations. Epidermal concentrations of magnesium (Mg) were strongly predictive in blubber, kidney and liver but only weakly predictive in muscle. Thus epidermal biopsy cannot predict elemental concentrations in four key tissues in bowhead whales in most cases. Cobalt (Co) and molybdenum (Mo) were not detected in any epidermal samples. This inability of epidermal element concentrations to reflect concentrations in internal tissues is likely true for other mysticetes and perhaps for cetaceans in general. At a minimum, before using epidermal biopsies to predict internal tissue concentrations of elements, researchers must establish that a sound scientific basis exists for doing so. Such proof must be specific to the elements, species and tissues in question as well as based upon statistically adequate sample sizes.